2000
DOI: 10.3390/50300549
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cyclic Di- and Triperoxides as Initiators of Styrene Polymerization at High Temperature with a View to Their Use in Industrial Applications

Abstract: Abstract:In industry, the bulk free radical polymerization of styrene takes place with the aid of peroxide initiators such as benzoyl peroxide. In this work di-and trimeric cyclic peroxides were used as initiators of the styrene polymerization in order to increase the rate of polymerization and molecular weights simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…22,23 These compounds can initiate polymerization of olefins and their utility as high temperature initiators is also under investigation. 24 Vennerstrom et al exploited medicinal potential of this class of compounds and have shown that some of the compounds are equally active as artemisinin. 19 Number of research papers have been published since then and little over 250 tetraoxanes have been evaluated for their antimalarial activity and some of the compounds have shown promising in vivo antimalarial activity.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 These compounds can initiate polymerization of olefins and their utility as high temperature initiators is also under investigation. 24 Vennerstrom et al exploited medicinal potential of this class of compounds and have shown that some of the compounds are equally active as artemisinin. 19 Number of research papers have been published since then and little over 250 tetraoxanes have been evaluated for their antimalarial activity and some of the compounds have shown promising in vivo antimalarial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Tetroxanes are capable of initiating polymerization of olefins and their utility as high temperature initiators is under examination [7]. More recently, tetroxanes have been found to posses an impressive antimalarial activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thermolysis of tetroxanes derived from cycloalkanones finds industrial use in the production of macrocyclic hydrocarbons and lactones [ 4 – 6 ]. Tetroxanes are capable of initiating polymerization of olefins and their utility as high temperature initiators is under examination [ 7 ]. More recently, tetroxanes have been found to posses an impressive antimalarial activity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%